Chloridomethyl(2-methylquinolin-8-olato-kappa 2 N,O)phenyltin(IV) - Vafaee, M.; Amini, M.M.; Ng, S.W. (International Union of Crystallography, 2010)
The asymmetric unit of the title complex, [Sn(CH(3))(C(6)H(5))(C(10)H(8)NO)Cl], consists of two independent molecules, both of which have the N,O-chelated SnIV atom in a cis-C(2)SnNOCl trigonal-bipyramidal geometry [C-Sn-C = 124.82 (8) and 137.69 (8)degrees]. The Cl atom of the molecule with the smaller C-Sn-C angle interacts weakly with the SnIV atom of the molecule with the wider C-Sn-C angle at an Sn...Cl distance of 3.595 (1) A. Weak intermolecular C-H...O and C-H...Cl hydrogen bonding is present in the crystal structure.